The Composition Effects of Tax-Based Consolidations on Income Inequality - Gabriele Ciminelli; Ekkehard Ernst; Massimo Giuliodori; Rossana Merola (Global Labor Organization (GLO), 2017)
Many advanced economies have recently embarked on fiscal austerity. As this has come at a time of high and rising income disparities, policy-makers have fretted about the inequality effects of fiscal consolidations. We shed new light on this issue by empirically investigating the (composition) effects of tax-based consolidations on income inequality, output and labour market conditions for a sample of 16 OECD countries over the period 1978-2012. We find that tax-based consolidations reduce income inequality, but at the cost of weaker economic activity. However, tax composition does matter. Indirect taxes reduce income inequality by more than direct taxes, possibly due to the operation of a positive labour supply channel. Higher indirect taxes increase the price of the consumption basket and create incentives for agents to increase their labour supply. We find this effect to be stronger for middle aged women. Looking at specific instruments, general consumption taxes and personal taxes are the most suited to reduce inequality while at the same time minimizing the equity-efficiency trade-off.
Keywords: E2; H2; O1; 330; Income distribution; Tax-based consolidation; Fiscal consolidation; Labour force participation; Tax composition